PENINGKATAN AKTIVITAS SISWA MENGGUNAKAN MODEL COOPERATIVE SCRIPT DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Prasetio, Okto; Hamimah, Hamimah; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of student activity Using Cooperative Script in learning IPS class VB SD Negeri 34 Simpang Haru. This research is Class action research  using qualitative and quantitative approaches. Research subjects were teacher and 20 students. Implementation of this research doing in two cycles with research procedural there are planning, implementation, observing, and reflection. Result of the reseacrh is showed increased : a) implementation, teacher aspects and student aspects of cycle I is 70,31%, and cycle II is 87,5%. b) student activities of cycle I : 1) visual activity 66,88%, 2) listening activity 66,88%  and  3) writing activity 73,75%. Cycle II :1) visual activity 87,50%, 2) listening activity 76,25% and 3) writing activity 88,75%. Conclusion of this reseacrh is model cooperative script can improve student activity in learning IPS class VB SD Negeri 34 Simpang Haru. keyword : Activity; Social studies; Cooperative Script